Ecological association between residential natural background radiation exposure and the incidence rate of childhood central nervous system tumors in France, 2000–2012. (January 2020) - Berlivet, Justine; Hémon, Denis; Cléro, Énora; Ielsch, Géraldine; Laurier, Dominique; Guissou, Sandra; Lacour, Brigitte; Clavel, Jacqueline; Goujon, Stéphanie
Abstract: Background: High-dose ionizing radiation is an established risk factor for childhood central nervous system tumors (CNST) but the role of low doses remains debated. In particular, there are few studies of natural background radiation (NBR, gamma radiation and radon) and childhood CNST, and their results are inconclusive. Objectives: This study aimed to investigate the ecological association between NBR exposure and childhood CNST incidence in France, considering childhood CNST overall and by subgroups. Methods: Incidence data were provided by the French national registry of childhood cancers, which has high completeness. We included 5471 childhood CNST cases registered over the period 2000-2012, and their municipality of residence at diagnosis was recorded. Municipality NBR exposures were estimated by cokriging models, using NBR measurements and additional geographic data. The incidence rate ratio (IRR) per unit variation of exposure was estimated with Poisson regression models. NBR exposures were considered at the time of diagnosis, and cumulatively from birth to diagnosis. In an exploratory analysis, the total brain dose due to NBR was used. Results: Overall, there was no association between NBR exposure and childhood CNST incidence (IRR = 1.03 (0.98, 1.09) per 50 nSv/h for gamma radiation, and IRR = 1.02 (0, 96, 1.07) per 100 Bq/m 3 for radon). An association was suggested between pilocytic astrocytomas and gamma radiation (IRR = 1.12 (1.00, 1.24) per 50 nSv/h) but not with radon (IRR = 1.07 (0.95, 1.20) per 100 Bq/m 3 ). Upward trends for this CNST subtype were also suggested with the cumulative exposures to gamma radiation and the total brain dose. NBR exposure was not associated with other CNST subgroups (ependymomas, embryonal tumors, and gliomas other than pilocytic astrocytomas). Adjustment for socio-demographic factors did not change the findings. Conclusions: Our study was based on high quality incidence data, large numbers of CNST cases, and validated models of NBR exposure assessment. Results suggest an association between gamma radiation, as a component of NBR, and pilocytic astrocytomas incidence in France. Highlights: Ecological study on childhood brain tumors and natural radiation in France. Complete nationwide recording of childhood brain tumors (5471 cases, 2000-2012). Cokriging models based on radiation measurements (>10, 000 sites) and geological maps. Gamma radiation associated with pilocytic astrocytoma incidence rate, not radon. Natural radiation not associated to ependymomas, embryonal tumors and other gliomas.